Knowledge of the ovulatory cycle and its determinants among women of childbearing age in Haiti: a population-based study using the 2016/2017 Haitian Demographic Health Survey - David Jean Simon; Yasmeen Jamali; Comfort Z. Olorunsaiye; Jean-Marie Théodat (BMC, 2023)
Abstract Background The knowledge of ovulatory cycle (KOC) is the base for natural family planning methods, yet few studies have paid attention to women's KOC. This study aimed to assess the prevalence of correct KOC and its determinants among women of childbearing age in Haiti. Methods Data from the nationally representative cross-sectional Haiti Demographic and Health Survey 2016/17 were used. STATA/SE version 14 was employed to analyse the data by computing descriptive statistics, Chi‑square, and binary logistic regression model to assess the socio-economic and demographic predictors of correct KOC. P-value less than 0.05 was taken as a significant association. Results Out of 14,371 women of childbearing age who constituted our sample study, 24.1% (95% CI 23.4-24.8) had correct KOC. In addition, the findings showed that place of residence, respondent's education level, wealth index, currently working, husband/partner's education level, contraceptive use, exposure to mass media FP messages, and fieldworker visit were significantly associated with correct KOC. Conclusion Policies should include increasing the literacy at community level as well as of individual women and their partners. Moreover, increasing awareness about family planning should be prioritized, especially for women from poor households and rural areas.